Multi-port DC circuit breaker based on dual capacitor current limiting and energy sink - Gu, Wei; Lou, Xiansi; Yin, Wenzhe; Huang, Qihang; Li, Shiqiang; Bian, Jing (Frontiers in Energy Research, 2023)
The coupling relationship between the fault current removal and the dissipation of residual energy of the fault line during fault isolation in multi-port capacitor-limited DC circuit breakers prolongs the fault opening time to a certain extent. To solve the above problems, this paper decouples the decay and removal process of fault current from the discharge process of residual energy of the fault line. It also proposes a multi-port DC circuit breaker based on dual capacitor current limiting and energy sink to further reduce the fault opening time and equipment withstand voltage requirements of DC circuit breakers. The proposed circuit breaker topology and operating principle are first analyzed, and then the parameters in the topology are designed. Subsequently, the simulation model is built in the PSCAD/EMTDC simulation platform, and the fault opening performance and opening time are calibrated to verify the effectiveness of decoupling the fault current removal process from the fault line residual energy discharge process to shorten the fault opening time.